Evaluating the role of electricity storage by considering short-term operation in long-term planning - Tom Brijs; Arne van Stiphout; Sauleh Siddiqui; Ronnie Belmans (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Short-term operating requirements and constraints in power systems are becoming increasingly important with the greater flexibility needed due to the integration of variable renewables. However, large problem sizes and computational barriers have limited the extent to which they are included in long-term planning models. Our objective is to understand the role of electricity storage in future renewable-based systems by including an accurate representation of short-term operation within a long-term planning framework. Specifically, we discuss the development of a long-term investment model including a continuous relaxation of the technology- clustered formulation of the short-term unit commitment problem. This model is applied to a test system having similar characteristics to the Belgian power system in a greenfield setting, i.e., assuming no pre-existing capacities, to analyze the role of storage at different renewable penetration levels. Both pumped-hydro storage and battery energy storage is considered, and their role in providing energy services and frequency control is investigated. We derive conclusions on the benefits and role of electricity storage to motivate why it may be built and operated. Results show that, in general, the integration of storage resources decreases total system cost, partially replaces flexible power plants, facilitates the integration of renewable energy sources, and allows inflexible technologies to perform better.
Keywords: C61; D4; L94; Q42; 330; electricity storage; renewable energy; power system flexibility; long-term power system planning; short-term power system operation